2014
DOI: 10.1182/blood.v124.21.571.571
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Tropomyosin 4 Cause Macrothrombocytopenia in Mice and Humans

Abstract: A genome-wide scan in nearly 70,000 individuals showed that the common SNP rs8109288 in the first intron of the human TPM4 gene exerts an effect on the volume and count of platelets (Gieger et al. Nature 2011). We isolated a mouse line with an ENU-induced missense mutation in Tpm4. Mice carrying this mutation exhibited dose-dependent macrothrombocytopenia, while other blood cell counts were normal. Bone marrow transplant experiments demonstrated that the phenotype is intrinsic to hematopoietic cells. Notably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The initial analysis could focus on all of the genes that are known to play a role in the regulation of platelet formation, i.e., their number and size. Indeed, the new powerful technologies that have been used during recent years provide evidence of new candidate genes regulating platelet biogenesis, such as TPM4 (Gieger et al , ), which was very recently found mutated in three pedigrees with macrothrombocytopenia (Pleines et al , ). Other genes remain to be identified, and no leads should be ruled out.…”
Section: New Candidate Genes For Unexplained Macrothrombocytopenias Imentioning
confidence: 99%
“…The initial analysis could focus on all of the genes that are known to play a role in the regulation of platelet formation, i.e., their number and size. Indeed, the new powerful technologies that have been used during recent years provide evidence of new candidate genes regulating platelet biogenesis, such as TPM4 (Gieger et al , ), which was very recently found mutated in three pedigrees with macrothrombocytopenia (Pleines et al , ). Other genes remain to be identified, and no leads should be ruled out.…”
Section: New Candidate Genes For Unexplained Macrothrombocytopenias Imentioning
confidence: 99%